Politics of waiting : Workfare, post-Soviet austerity and the ethics of freedom - Ozolina, Liene (Book collections on Project MUSE., 2019)
"This book is an ethnography of the politics of waiting. While the global political economy is usually imagined through metaphors of acceleration and speed, Ozolina's book reveals waiting as the shadow temporality of the contemporary logic of governance. The ethnographic site for this analysis is a state-run unemployment office in Latvia. This site not only grants the author unique access to observing everyday implementation of social assistance programmes that use acceleration and waiting as forms of control, but also serves as a vantage point from which to compare Western and post-Soviet welfare policy designs. The book thus contributes to current debates across sociology and anthropology around the increasingly coercive forms of social control, by examining ethnographic forms of statecraft that have emerged over several decades of neoliberalism. The ethnographic perspective reveals how time shapes a nation's identity, as well as one's sense of self, in culturally specific ways. The book traces how both the Soviet past, with its narratives of building communism at an accelerated speed while waiting patiently for a better future, as well as the post-Soviet nationalist narratives of waiting as a sacrifice for freedom, come to play a role in this particular case of the politics of waiting. This book will be essential reading for students and scholars interested in contemporary forms of state power, temporal politics, and political subjectivity formation, as well as comparisons between Western and post-Soviet welfare reforms." -- Back cover.